Evaluation of antianxiety effect of cinnamaldehyde in swiss albino mice - Churihar, Ritesh; More, Sapna A.; Mishra, Pooja S.; Vyas, Savita; Tanwani, Hemant (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Cinnamon is one of the best known spices used as an herbal medicine. Cinnamaldehyde (CNM) the volatile oil, which was present in the essential oil of the bark, is the important constituents of cinnamon. Cinnamon has been investigated for its various effects like peptic ulcer protection, antioxidant property, inhibition of tau aggregation, anti-inflammatory activity, effect on cardiovascular system, anti-nociceptive activity, hepato-protective effects, hypolipidemic and antidiabetic activites. The present study was aimed to evaluate the anxiolytic effect of CNM per se and its interaction with diazepam in swiss albino mice. Methods: Anxiolytic activity was evaluated by elevated plus maze method. A group of 36 healthy mice of either sex weighing 20-30 grams were divided at random into six groups (n=6). CNM and diazepam were dissolved in tween twenty 20% to maintain uniformity of the solvent and given orally. Group I was given twenty 20% (10 ml/kg, p.o.), group II diazepam (0.5 mg/kg, p.o.), group III diazepam (1 mg/kg, p.o.), group IV cinnamaldehyde (100 mg/kg, p.o.), group V cinnamaldehyde (200 mg/kg, p.o.), group VI cinnamaldehyde and diazepam (100 mg/kg and 0.5 mg/kg, p.o.). Results: Cinnamaldehyde per se showed no anxiolytic effect at any dose (p<0.05). The standard drug diazepam has shown significant anxiolytic activity on elevated plus maze. Whereas combination of diazepam 0.5 mg/kg and cinnamaldehyde 100 mg/kg showed significant increase in the time spent in open arms as compared to all groups (p<0.05). Conclusions: CNM per se did not show any effect on anxiety but enhanced the action of diazepam when co-administered.